2021
DOI: 10.3390/nu13020548
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Levels of Zinc, Copper, and Iron with Risk of Metabolic Syndrome

Abstract: The association between serum concentrations of zinc, copper, or iron and the risk of metabolic syndrome are inconclusive. Therefore, we conduct a case-control study to explore the relationship between serum levels of zinc, copper, or iron and metabolic syndrome as well as each metabolic factor and insulin resistance. We enrolled 1165 adults, aged ≥ 40 (65.8 ± 10) years in a hospital-based population to compare the serum levels of zinc, copper, and iron between subjects with and without metabolic syndrome by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 36 publications
2
19
1
Order By: Relevance
“…It is worth noting that Luciano-Mateo et al [ 27 ] observed reduced levels of Ca, Fe, Mg, Na, and Zn and increased levels of some trace elements in serum (e.g., Sr) in women with giant obesity. In a study by Lu et al [ 73 ], higher serum levels of Zn, Cu, and Fe were associated with the risk of MetS. In addition, serum levels of Zn, Cu, and Fe increased with a rise in the number of metabolic factors ( p < 0.001).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is worth noting that Luciano-Mateo et al [ 27 ] observed reduced levels of Ca, Fe, Mg, Na, and Zn and increased levels of some trace elements in serum (e.g., Sr) in women with giant obesity. In a study by Lu et al [ 73 ], higher serum levels of Zn, Cu, and Fe were associated with the risk of MetS. In addition, serum levels of Zn, Cu, and Fe increased with a rise in the number of metabolic factors ( p < 0.001).…”
Section: Discussionmentioning
confidence: 97%
“…The IMMIDIET study in Europe and the NHANES study in Korea [ 74 ] found no association between serum Zn levels and MetS. In contrast, Lu et al [ 73 ] reported a strong positive association between Zn and MetS, suggesting impaired Zn homeostasis in patients with MetS in addition to insulin resistance and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Serum copper and zinc and the ratio of Zn/Cu are often used to identify oxidative stress and inflammation ( 119 , 120 ). Furthermore, protein chaperones, such as heat shock proteins (HSP) are highly expressed during oxidative stress ( 121 ).…”
Section: Other Clinical Studiesmentioning
confidence: 99%
“…Furthermore, protein chaperones, such as heat shock proteins (HSP) are highly expressed during oxidative stress ( 121 ). Some recent studies reported the effects of curcumin and its derivatives on some oxidative stress markers in MS patients ( 122 ), for instance, serum copper, zinc, and trace elements are elevated in patients with MS compared to healthy subjects ( 120 ). A double-blind clinical trial of 120 subjects with MS reported increased serum zinc and Zn/Cu ratio after administration of curcumin and phospholipid curcumin complex at a dose of 1 g/day for 6 weeks ( 123 ).…”
Section: Other Clinical Studiesmentioning
confidence: 99%
“…The last 2 ml were examined for the levels of micronutrients in serum (zinc (Zn), iron, and copper (Cu) levels) by using the Spectrophotometer (ICP-OES Optima 2X00/7000 Series DV, PerkinElmer, Waltham, Massachusetts, USA). Results were expressed as µg/dl (Lu et al 2021).…”
Section: Blood Sampling Techniquementioning
confidence: 99%